Reflections on Motherhood and Earning a Doctorate: Yes, You Can Have it All (Just Add a Dash of Superwoman) - Kirby Grabowski (Working Papers in Applied Linguistics and TESOL, 2015)
On more than one occasion, I’ve heard that writing a dissertation is comparable to giving birth. After having just given birth to a dissertation and a baby within a couple of months, I can say that writing a dissertation is decidedly nothing like having a baby. One of the most obvious differences is that at the end of the day, you don’t get to “hand in” your real baby to the folks in the Office of Doctoral Studies after you’ve been up all night for months! However, upon further reflection (and the fortuitous phenomenon that leaves your mind absent of any memories of the birth soon after the fact), I do see a couple of similarities. The first is that you get to be part of an exclusive club only made up of moms who know exactly what you have been through to get to the other side. The second similarity is that, whether dissertation or child, you pour your heart and soul into your “baby.” In both cases, the beautiful fruits of your labor are a part of you forever.